2019
DOI: 10.1111/1759-7714.13075
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow dose computed tomography protocol for hook‐wire localization of solitary pulmonary nodules prior to video‐assisted thoracoscopic surgery

Abstract: Background This study prospectively investigated the efficacy and radiation dose of ultralow dose computed tomography (CT)‐guided hook‐wire localization (HWL) at 100 kV with tin filtration (100Sn kV) for small solitary pulmonary nodules. Methods All HWL procedures were performed on a third generation dual‐source CT system. Eighty‐eight consecutive patients undergoing CT‐guided HWL were randomly assigned to standard dose CT (Group A: n = 44; re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This study has several limitations. First, some previous studies (4,22,23) reported a slightly higher radiation dose reduction than ours using the tin filter technique. The cause for this difference might be that those studies used a third-generation dual-source system, which contains more advanced hardware and software than our normal clinicaluse CT scanner.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This study has several limitations. First, some previous studies (4,22,23) reported a slightly higher radiation dose reduction than ours using the tin filter technique. The cause for this difference might be that those studies used a third-generation dual-source system, which contains more advanced hardware and software than our normal clinicaluse CT scanner.…”
Section: Discussionmentioning
confidence: 51%
“…Tin filtration has the potential to reduce the radiation dose. Previous studies (22,23) used a tin filter to reduce the radiation dose during CT-guided biopsy procedures using 100 kVp in a third-generation dual-source CT system, with a dose reduction of 90%. Compared with the routinedose protocol, our low-dose protocol with a tin filter at 130 kVp yielded a 73.2% reduction per scan, which is consistent with the radiation dose reductions of 53.3-94.5% reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…VATS is a mature minimally invasive surgical technique. A number of studies [ 11 , 12 ] showed that VATS is easier to be accepted by physicians and patients in the process of clinical application because it has both small wounds, light postoperative pain, and complications. The advantages are fewer symptoms and faster recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided percutaneous hookwire localization appeared earlier and has been widely used globally. Reportedly, hookwire localization has a high success rate [ 18 ]. It was also the most prominent preoperative PN positioning method used in our unit.…”
Section: Discussionmentioning
confidence: 99%